New approach to development aid - Tibor Mende (Intereconomics, 1972)
The prevailing disenchantment concerning the less developed countries (LDCs) has multiple roots. Two, however, are of particular importance. The first, symbolised by the report of the Club of Rome, is connected with the implications of the world's finite resources. The second, underlined by Mr McNamara, is in the obstinately and grossly unequal distribution of the benefits of whatever progress is being made.
Keywords: 330; Development Policy